Determining the Pricing Strategy and Pricing the Products of Mobile Games: Mathematical Model Approach. (18th August 2022) - Budak, Gerçek; Özen, Barış
Abstract : In the technology era, new sectors, occupations, and products or services related to technology arise. Mobile gaming industry is one of those sectors with the technological developments of personal mobile devices. This sector is rapidly growing in terms of the number of companies, employees, games, and financial income; however, this situation increases the competition and companies in this sector survive as if they succeed a sustainable profit from the game by selling their products or services. These products can be grouped into four which are the game itself, cosmetic products, in-application purchases, and advertisements or product placements during the gameplay. This study outlines a two-staged decision process for deciding which products should be priced and how much they should be charged for every customer. The first stage is an enumeration of all sixteen alternatives of pricing strategies for four products which are game, in-game boost-ups, cosmetics and advertisements, and expert decision to choose among those alternatives which would fit to the concerned mobile game. In the second stage, a mathematical model is used to price for obtaining the maximum profit for the company. Another mathematical model is also proposed for pricing the products differently for each customer according to their psychological player profile as if the decision-maker prefers such a pricing strategy. Implication and extensions of the models are discussed, and their real-life application is also presented in the study.